Desarrollo e implementación de un plan de continuidad del negocio para una entidad educativa privada para el año 2009. - Guarochico Moreira, Camilo Gabriel (2009)
This work is to undertake a comprehensive analysis of the functions, processes and procedures of a private educational institution, with the purpose of designing and implementing a Business Continued Planning (BCP), to perform an analysis about possible threats and risks facing the entity education, for in this way to provide standard procedures to apply in the event that any of these eventualities occur. To find an administrative and financial analysis about the effect of these threats and risks, to identify the highest impact. We analyze the feasibility and improvement of the alternatives selected and thus minimized the impact on the normal functioning of the body and protects the security physical and mental of staff and customers.